DETERMINAN AUDIT JUDGMENT PADA AUDITOR PEMERINTAH - Hernawan Harsono; Syarif M Helmi; Leonardus Acon (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2023)
This study aims to determine the effect of audit experience, audit expertise, and task complexity on audit judgment. The research was conducted at Badan Pengawasan Keuangan dan Pembangunan (BPKP) Perwakilan Provinsi Kalimantan Barat. The data yang used in this study is the primary data in the form of questionnaire data. Audit experience, expertise, task complexity, and judgment are measured on a Likert score scale of 1-5. This research uses quantitative analysis methods, including descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression, T-tests, F tests, and coefficient of determination tests (R2). The results of this study show that audit experience and expertise do not affect audit judgment. Meanwhile, the complexity of the task affects the audit judgment.